Beyond Water Splitting: Efficiencies of Photo‐Electrochemical Devices Producing Hydrogen and Valuable Oxidation Products. Issue 1 (16th January 2017) - Mei, Bastian; Mul, Guido; Seger, Brian
Abstract : Coproduction of valuable chemicals such as halides or hydrogen peroxide concomitant with hydrogen production is presented as a strategy to boost the industrial applicability of photo‐electrochemical and photocatalytic systems. Highly efficient two‐photon devices can be fabricated (solar‐to‐chemical efficiencies of >27%), whereas single absorber devices will be appropriate for, for example, HBr splitting and efficiencies of almost 19% can be obtained.